Climate and Nothofagus pumilio Establishment at Upper Treelines in the Patagonian Andes - Srur, Ana M.; Villalba, Ricardo; Rodríguez-Catón, Milagros; Amoroso, Mariano M.; Marcotti, Eugenia (Frontiers in Earth Science, 2018)
Due to its climate sensitivity, the upper treeline offers a unique opportunity to document variations in forest dynamics in response to current climate change. It is generally accepted that the expansion of the upper treeline is limited by cold temperatures. Consequently, warmer conditions in the context of global warming are expected to induce an advance of forests into alpine vegetation. To complement previous studies in the North Patagonia treeline, we conducted a study in the southern Patagonian Andes to: 1) characterize the temporal patterns of Nothofagus pumilio establishment in the upper treeline along a precipitation gradient, 2) establish the relationship between variations in regional climate and tree establishment, and 3) determine the influence of continental and hemispheric-scale climatic forcing on tree establishment at regional scale. At El Chaltén-Laguna del Desierto area, the N. pumilio establishment above the upper treelines started at the mid-1970s and reached two peaks in the late 1980s-early 1990s and around the year 2000. Although tree establishment followed similar patterns along the precipitation gradient, we noted some differences between wet and dry forests. Whereas at the wettest sites the largest establishment peak occurred in the most recent, relatively-dry period, tree recruitment was more abundant in the earliest humid period at the driest treelines. Our studies suggest that the location of the N. pumilio upper treeline in the Patagonian Andes is sensitive to changes in climate. The increment in temperature during the past decades has facilitated tree recruitment; however, the rate of seedling establishment appears to be modulated by interactions between the temperature increase and variations in precipitation. The expansion of the upper treeline is mostly limited to 5-10 m from the abrupt treeline suggesting that seed dispersal and winds modulate the rate of spatial advance. While the recent expansion of the upper treeline in northern Patagonia was regulated by temperature and precipitation variations associated with the different phases of the Pacific Decadal Oscillation, the climatic variations induced by the positive trend of the Southern Annular Mode during the last decades have facilitated the establishment above the upper treeline in the southern Patagonian Andes.